Effector cell signature in peripheral blood following nasal allergen challenge in grass pollen allergic individuals. Issue 2 (February 2015) - Shamji, M. H.; Bellido, V.; Scadding, G. W.; Layhadi, J. A.; Cheung, D. K. M.; Calderon, M. A.; Asare, A.; Gao, Z.; Turka, L. A.; Tchao, N.; Togias, A.; Phippard, D.; et al.
Abstract Background Several studies have demonstrated the time course of inflammatory mediators in nasal fluids following nasal allergen challenge (NAC), whereas the effects of NAC on cells in the periphery are unknown. We examined the time course of effector cell markers (for basophils, dendritic cells and T cells) in peripheral blood after nasal grass pollen allergen challenge. Methods Twelve participants with seasonal allergic rhinitis underwent a control (diluent) challenge followed by NAC after an interval of 14 days. Nasal symptoms and peak nasal inspiratory flow (PNIF) were recorded along with peripheral basophil, T‐cell and dendritic cell responses (flow cytometry), T‐cell proliferative responses (thymidine incorporation), and cytokine expression (FluoroSpot assay). Results Robust increases in nasal symptoms and decreases in PNIF were observed during the early (0–1 h) response and modest significant changes during the late (1–24 h) response. Sequential peaks in peripheral blood basophil activation markers were observed (CD107a at 3 h, CD63 at 6 h, and CD203cbright at 24 h). T effector/memory cells (CD4+CD25lo) were increased at 6 h and accompanied by increases in CD80+ and CD86+ plasmacytoid dendritic cells (pDCs). Ex vivo grass antigen‐driven T‐cell proliferative responses and the frequency of IL‐4+CD4+ T cells were significantly increased at 6 h after NAC when compared to the control day. Conclusion Basophil, T‐cell, and dendritic cell activation increased the frequency of allergen‐driven IL‐4+CD4+ T cells, and T‐cell proliferative responses are detectable in the periphery after NAC. These data confirm systemic cellular activation following a local nasal provocation.